International migration of couples - Marin Junge; Martin D. Munk; Panu Poutvaara (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
We develop a theoretical model regarding the migration of dual-earner couples and test it in the context of international migration. Our model predicts that the probability that a couple emigrates increases with the income of the primary earner, whereas the income of the secondary earner may affect the decision in either direction. We conduct an empirical analysis that uses population-wide administrative data from Denmark, and the results are consistent with our model. We find that primary earners in couples are more strongly self-selected with respect to income than single persons. This novel result counters the intuition that family ties weaken self-selection.
urn:nbn:de:bvb:19-epub-24924-7
Keywords: F22; J12; J16; J24; 330; International migration; Family migration; Education; Gender differences; Dual-earner couples; Beauty; Elections; Political candidates; Appearance; Ideology; Parties